Modulation of GABAergic transmission in development and neurodevelopmental disorders: investigating physiology and pathology to gain therapeutic perspectives - Deidda, Gabriele; Bozarth, Ignacio F.; Cancedda, Laura (Frontiers in Cellular Neuroscience, 2014)
During mammalian ontogenesis, the neurotransmitter GABA is a fundamental regulator of neuronal networks. In neuronal development, GABAergic signaling regulates neural proliferation, migration, differentiation, and neuronal-network wiring. In the adult, GABA orchestrates the activity of different neuronal cell-types largely interconnected, by powerfully modulating synaptic activity. GABA exerts these functions by binding to chloride-permeable ionotropic GABAA receptors and metabotropic GABAB receptors. According to its functional importance during development, GABA is implicated in a number of neurodevelopmental disorders such as autism, Fragile X, Rett syndrome, Down syndrome, schizophrenia, Tourette's syndrome and neurofibromatosis. The strength and polarity of GABAergic transmission is continuously modulated during physiological, but also pathological conditions. For GABAergic transmission through GABAA receptors, strength regulation is achieved by different mechanisms such as modulation of GABAA receptors themselves, variation of intracellular chloride concentration, and alteration in GABA metabolism. In the never-ending effort to find possible treatments for GABA-related neurological diseases, of great importance would be modulating GABAergic transmission in a safe and possibly physiological way, without the dangers of either silencing network activity or causing epileptic seizures. In this review, we will discuss the different ways to modulate GABAergic transmission normally at work both during physiological and pathological conditions. Our aim is to highlight new research perspectives for therapeutic treatments that reinstate natural and physiological brain functions in neuro-pathological conditions.